Country Partnership Framework for Zambia for the Period FY19 - FY23 - World Bank Group (World Bank, Washington, DC, 2019)
This Country Partnership Framework (CPF) proposes to assist the Government's efforts to rekindle economic growth while following a more inclusive and sustainable path. Poverty in Zambia is severe compared to its peers, reflecting high inequality levels. The CPF program is organized around three focus areas: rural development, human capital investments, and improved public financial management.